Joias para os museus da história: o acervo documental sobre a Revolução Farroupilha e o Arquivo Histórico do Rio Grande do Sul (1925-1940) - Arce, Ana Inés (2015)
This work seeks to assess the incorporation of collections concerning the Farroupilha Revolution into the Historical Archive of Rio Grande do Sul (which operated beside the Júlio de Castilhos Museum between 1925 and 1954) in the period around the celebrations of the Farroupilha Centennial (1935). Such period was marked by the 1930 Revolution and Getúlio Vargas’s government, by disputes between the federal and state governments, and the new place of Rio Grande do Sul in the national context. A period when political issues were accompanied as well by a glowing dispute raged in the historiographical field. The Civil War of 1835 was re-updated from the vantage point of the present, and the historiographical views that tended to see the movement as more autonomous gave way to more integrative positions. Thus, the work seeks, first, to situate the documental production of the Farroupilha Decade and follows the archival history of private and public collections. It introduces the main memory institutions of the State of Rio Grande do Sul, the Júlio de Castilhos Museum (MJC) and the Historical and Geographical Institute. It analyzes the gathering of collections concerning the Farroupilha Period prior to the Centennial. It contextualizes the political moment of the 1920s and 1930s and the insertion of the state of Rio Grande do Sul in the national context. It dwells on the celebrations around the Farroupilha Centennial and the disputes that ensued regarding the character of the Revolution. It analyzes the mobilization of the Historical Archive (MJC) around this event, particularly the strategies used to increase its collection, highlighting the incorporation of the Varela Collection. It seeks to outline a picture of the historical studies and intellectuals of Rio Grande do Sul in the 1920s and 1930s. It analyzes the role of the Historical Archive and its archivist Eduardo Duarte, in this context. And finally, it makes some considerations about the theoretical and methodological conceptions that could have influenced the choices that eventually shaped the documental patrimony of this inescapable episode of our history.